ANALISIS KEBIJAKAN PENDIDIKAN TERKAIT IMPLEMENTASI PEMBELAJARAN PADA MASA DARURAT COVID 19 - Irwan Irwan; Fauqa Nuri Ichsan; Nurhizrah Gistituati; Sufyarma Marsidin (Universitas Pakuan, 2021)
ANALYSIS OF EDUCATIONAL POLICY RELATED TO THE IMPLEMENTATION OF LEARNING IN THE EMERGENCY OF COVID 19This study that was utilising a descriptive research approach was intended to factually and accurately describing the facts, the nature and also the relationship among the phenomena of the research object. The purpose of this descriptive research was to generate a systematic, factual and accurate description of the available facts, characteristics and relationships among the phenomena. The type of descriptive method used was library research. Library research is an activity of observing various literatures related to the issues arose in the form of books, papers and writings that may help researchers so they can be used as guidelines in the research process. This study was intended to determine (1) the distance learning system that might be applied, (2) the impact of the distance learning system on student achievement, (3) the obstacles in the implementation of the distance learning system. The research method used in this study was a qualitative method with a qualitative descriptive approach. The results of this study indicated that the implementation of distance learning was still fasing many obstacles such as inadequate tools and poor internet connection. Beside that the gaining of learning success was still small and ineffective.